PREPARATION AND CHARACTERIZATION OF ARTESUNATE - NICOTINAMIDE COCRYSTAL BY SOLVENT EVAPORATION AND SLURRY METHOD - SETYAWAN, DWI; SARI, RETNO; YUSUF, HELMY; PRIMAHARINASTITI, RIESTA (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The present study aims to prepare and characterize cocrystals of artesunate (AR) - nicotinamide (NI) in order to improve bioavailability and efficacy of artesunate as an antimalarial drug. Methods: Cocrystals were prepared using solvent evaporation and slurry methods. Physicochemical characterizations were performed using Hot Stage Microscope (HSM), infrared spectroscopy (IR), thermal analysis DTA, X-Ray Powder Diffraction (PXRD) and Scanning Electron Microscope (SEM). Results: The study revealed that re-crystallization of AR, NI and a physical mixture of both compounds showed distinctive shapes as shown by HSM microscope. AR has a needle shape, whereas NI showed mosaic spherulite crystal. Furthermore, as the two compounds experienced a contact one another, new crystals i.e. fiber-like shape were observed, indicating formation of a cocrystal of AR-NI was successfully achieved. Two different molar ratios of AR-NI from the phase diagram (i.e. 50:50 and 60:40 percent) showed a decrease in the melting temperature i.e. 104.0°C and 104.7°C, respectively, in comparison with the melting point of the constituent materials (AR 133.6°C and NI 142.2°C). PXRD diffractogram showed that cocrystal of AR–NI exhibited new diffraction peaks at 2q = 5,8°; 17,4° and 17,8°, whereas no peaks were found for physical mixtures of AR - NI. Characterization with IR showed disappearance of transmission peaks at 2976 and 2639 cm-1 indicating a loss of NH3+ bending bands. Furthermore, disappearance of C=O stretch at 1346 cm -1 and -OH bending at 1485 cm -1 indicated a formation of hydrogen bonding between AR and NI. This was due to the formation of cocrystals prepared by solvent evaporation method, since the cocrystals made by the slurry method only showed the loss of NH3+ at 2639 cm-1. SEM micrographs showed that co-crystals prepared by solvent method have a more homogeneous mixture of AR-NI compared to the cocrystal formed by slurry method. Conclusion: The study concludes that cocrystals of AR-NI were successfully formed using solvent evaporation and slurry methods. The formed co-crystals of AR - NI exhibited different physicochemical characteristics as compared to the constituent materials. The formed cocrystals prepared by solvent evaporation method have a lower melting point and relatively more homogeneous in terms of crystal composition. Keywords: characterization, artesunate, nicotinamide, cocrystal, solvent evaporation method, slurry method